2020
DOI: 10.1186/s13071-020-3880-2
|View full text |Cite
|
Sign up to set email alerts
|

Bionomics and insecticide resistance of Aedes albopictus in Shandong, a high latitude and high-risk dengue transmission area in China

Abstract: Background: Dengue fever outbreaks tend to spread northward in China, and Jining is the northernmost region where local dengue fever cases have been detected. Therefore, it is important to investigate the density of Aedes albopictus and its resistance to deltamethrin. Methods: The Breteau index (BI) and container index (CI) were calculated to assess the larval density of Ae. albopictus and human-baited double net trap (HDN) surveillance was performed in six subordinate counties (Rencheng, Yanzhou, Sishui, Lian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 40 publications
1
37
0
1
Order By: Relevance
“…Beijing-Guangzhou railway, Beijing-Shanghai railway, and Beijing-Kowloon railway, etc.). All these results revealed that human-aided dispersion might be the main reason for the similarity of populations across the different regions [22,[67][68][69][70][71][72][73][74][75][76][77][78]. This hypothesis was also veri ed via IBD analysis, which indicated that long distances were not signi cantly associated with individual genetic variation, except among individuals from the tropical region with a signi cant p-value of the Mantel test.…”
Section: Discussionmentioning
confidence: 96%
“…Beijing-Guangzhou railway, Beijing-Shanghai railway, and Beijing-Kowloon railway, etc.). All these results revealed that human-aided dispersion might be the main reason for the similarity of populations across the different regions [22,[67][68][69][70][71][72][73][74][75][76][77][78]. This hypothesis was also veri ed via IBD analysis, which indicated that long distances were not signi cantly associated with individual genetic variation, except among individuals from the tropical region with a signi cant p-value of the Mantel test.…”
Section: Discussionmentioning
confidence: 96%
“…Beijing-Guangzhou railway, Beijing-Shanghai railway and Beijing-Kowloon railway). All these results revealed that human-aided dispersion might be the main reason for the similarity of populations across the different regions [ 25 , 70 – 74 , 77 83 ]. This hypothesis was also verified via IBD analysis, which indicated that long distances were not significantly associated with individual genetic variation, except among individuals from the tropical region with a significant p value of the Mantel test.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing levels of PyR are reported also in Ae. albopictus , both in its native and invasive range, with particular reference to the Indian subcontinent and Africa [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. There is also growing evidence for PyR emerging in Ae.…”
Section: Introductionmentioning
confidence: 99%